Static and fatigue behavior of plug-welded dissimilar metal welds between carbon steel and austenitic stainless steel with different thicknesses - Farah Nadhirah (International Journal of Mechanical and Materials Engineering, University of Malaya, 2014)
Background: Plug welding was used on the parts of the structure in which spot welding cannot be implemented, such as the complex structure and the construction with the profile stiffener. The objective of the present work is to define the static and fatigue behaviors of the plug-welded dissimilar metal welds between carbon steel and austenitic stainless steel with different thicknesses because the detailed recommendations on it were limited.